ANALISISSIKAPKONSUMENTERHADAPPONSELNOKIADIKOTAJAMBI (THEANALYISOFCONSUMERATTITUDEONCELLULERPHONEINJAMBICITY - Tri Rahayu Aguswindi (DIGEST MARKETING, 2012)
TheresearchpurposeistoexplainandanalysistheconsumersattitudeofNokiaCellulerphoneinJambiCity.Theamountofsampleis100Nokiasuser,thatchosenwithconveniencemethod.Theconsumersattitudeusedbeliefandevaluationconcepttosomeimportantattributes.Theattributesarebrand,taste,quality,feature,priceandpromotion.ThisresearchreccomendationtothecorporationisconsideringtheattributesthatshowslessvalueontheFishbenconceptbedeveveloped.Keywords.Consumerattitude,likertscaleandproductfeature